Upaya Meningkatkan Kemampuan Membaca Permulaan Kelas 1 SD/MI dengan Metode Iqro di Madrasah Ibtidaiyah Al Hikmah Purwodadi Belitang Mulya OKU Timur - Sri Enggar Kencana Dewi; Ratih Purnama Pertiwi (Jurnal Indonesia Mengabdi, 2019)
One of the goals is to provide early reading learning for elementary / MI children in the lower classes, namely classes 1, 2 and 3. The learning process especially reads at MI Al-Hikmah Purwodadi, who still uses the manual method by spelling with letters that students already know making students a little confused because they don't really understand the letters of the alphabet. Most of the students of Al-Hikmah Purwodadi were mostly recited at the TPA so that the students understood the hijaiyah letters more than the letters of the alphabet. Many students face difficulties in reading the beginning because of the background of students who are not from kindergarten graduates. As a solution to provide convenience for students who read the beginning and for MI Al-Hikmah Purwodadi teachers to simplify the learning process by using motivational and interesting methods and media to learn to read the beginning. In this service the method used is the iqra method. The results and benefits of service are increasing reading interest in MI Al Hikmah Purwodadi students, increasing knowledge and understanding of 1st grade students of MI Al-Hikmah Purwodadi in reading, increasing reading skills in class 1 MI Al-Hikmah Purwodadi. Keywords: Reading Beginning, Iqra Method